Pengukuran Risiko Operasional Pada Bank Syariah Indonesia (Studi Kasus Bank Syariah XYZ) - Yudi Yudiana; Didin Hafidhuddin; Rifki Ismal (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2018)
The research aimed at calculating the Operational Value at Risk (OpVar) in estimating the probability of the frequency of losses at Sharia Bank of XYZ, analyzing and assessing the event types of operational risks which have a great contribution in the operational losses of the bank, and determining the efficiency levels of the operational value at risk of capital charges of the bank. Measurement of operational risk in this study was conducted using the Loss Distribution Approach (LDA) Aggregated Model, as one of the Advanced Measurement Approach (AMA) models, which theoretically produces more efficient capital charges. The results showed that the contribution of the biggest losses came from the events of business disruption and system failure, execution, delivery & process management and internal fraud. The calculation of the operational risk of the bank conducted using the LDA-Aggregate produced lower capital charges than those using the Basic Indicator Approach.Keywords: Islamic bank, operational risk measurement, advanced measurement approach, loss distribution approachAbstrak: Penelitian ini bertujuan melakukan perhitungan Operational Value at Risk (OpVaR) untuk mengestimasi peluang kejadian kerugian (probability of the frequency of losses) di bank syariah xyz; menganalisis dan mengevaluasi tipe kejadian risiko operasional yang berkontribusi besar pada kerugian operasional bank syariah xyz; menentukan besarnya tingkat efisiensi beban modal risiko operasional bank syariah xyz. Pengukuran risiko operasional dalam penelitian ini menggunakan Loss Distribution Approach (LDA) Aggregated Model sebagai salah satu internal model Advanced Measurement Approach (AMA) yang secara teori menghasilkan beban modal yang lebih efisien. Hasil penelitian menunjukkan kerugian terbesar terdapat pada tipe kejadian business disruption & system failure, execution, delivery & process management dan internal fraud. Perhitungan risiko operasional bank syariah xyz dengan menggunakan Metode LDA-Aggregate menghasilkan beban modal yang lebih rendah dibandingkan dengan penggunaan metode Basic Indicator Approach.Kata kunci: bank syariah, pengukuran risiko operasional, advanced measurement approach, loss distribution approach